2020
DOI: 10.3390/math8101725
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Comparing COVID-19 Intervention Strategies Using a Varying Partial Consensus Fuzzy Collaborative Intelligence Approach

Abstract: The COVID-19 pandemic has severely impacted our daily lives. For tackling the COVID-19 pandemic, various intervention strategies have been adopted by country (or city) governments around the world. However, whether an intervention strategy will be successful, acceptable, and cost-effective or not is still questionable. To address this issue, a varying partial consensus fuzzy collaborative intelligence approach is proposed in this study to assess an intervention strategy. In the varying partial consensus fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…To tackle this, some fuzzy or probabilistic decision-making methods [ 46 , 47 , 48 ] have been proposed. For example, Wu et al [ 10 ] proposed a fuzzy collaborative intelligence-based fuzzy analytic hierarchy process (FAHP) approach to evaluate and compare fifteen intervention strategies in response to the COVID-19 pandemic. In their methodology, each expert applies the FGM method to evaluate the relative priorities of criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle this, some fuzzy or probabilistic decision-making methods [ 46 , 47 , 48 ] have been proposed. For example, Wu et al [ 10 ] proposed a fuzzy collaborative intelligence-based fuzzy analytic hierarchy process (FAHP) approach to evaluate and compare fifteen intervention strategies in response to the COVID-19 pandemic. In their methodology, each expert applies the FGM method to evaluate the relative priorities of criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This task can be regarded as a fuzzy group multi-criteria decision-making problem [ 8 , 9 ] for the following reasons. First, it is clear that there are many uncertainties associated with the COVID-19 pandemic, which are mainly caused by the human intervention [ 10 ]. Fuzzy sets, such as ordinary fuzzy sets [ 11 , 12 ], intuitionistic fuzzy sets [ 13 ], interval type-2 fuzzy sets [ 14 ], and hesitant fuzzy sets [ 15 ], are particularly useful for dealing with this type of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy collaborative intelligence has also been applied to fuzzy analytic hierarchy process problems, in which the priorities derived by experts or the overall performances evaluated by them were aggregated using FI [28][29][30][31], PCFI [31][32], evolving (or layered) PCFI (EPCFI or LPCFI) [33], or FWI [34].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Singapore’s experience has shown that migrant workers living in dormitories face additional health risks [ 48 ], because they may be from countries with the severe COVID-19 pandemic or be infected while taking airplanes or living in dormitories. Most short-term preventive measures and intervention strategies, such as wearing masks, physical distancing, periodic disinfection, and regular temperature checks, are designed to reduce such risks [ 49 ]. Supply chain breakage: The COVID-19 pandemic has caused the closures of factories around the world, many of which are located in the upstream or midstream segments of supply chains [ 50 ].…”
Section: Factors Influencing the Robustness Of A Factory To The Comentioning
confidence: 99%
“…Their combination is not easy to calculate. To tackle such complexity, is approximated with a TFN as [ 49 ]: where , , and denote the minimum, center of gravity (COG) [ 65 ] and maximum of , respectively: as illustrated in Figure 7 . In this way, the defuzzified value of the approximating TFN is equal to .…”
Section: The Fuzzy Collaborative Intelligence Approachmentioning
confidence: 99%